Methodological Approach to Assessing the Activities of a Social Enterprise on Emerging Markets - Wlodzimierz STRELCOW; Jaroslaw SZREDER (Communications of International Proceedings, 2022)
The article considers the features of social entrepreneurship in the context of the emergence of climate crisis in developing countries. The measurement of performance and impact at different levels are among the most important challenges for studies in the field of social enterprises. The article is based on an analysis of the literature on the subject taking into account the most frequently cited models in the literature and used by social enterprises: the Social Return On Investment (SROI) and the Social Balanced Scorecard (SBSC). One of the important gap that must be addressed is the lack of impact metrics tracking and regular measurement. Empirical study showed main challenges with combining qualitative and quantitive  results of the activity of a social enterprise.  Most important findings are connected with proposed scheme of assessment, which include 8 indicators of economic, social and environmental activity.
Keywords: social enterprises; social entrepreneurship; ecology; impact metrics